Antioxidants in Varieties of Chicory (Cichorium intybus L.) and Wild Poppy (Papaver rhoeas L.) of Southern Italy. (16th March 2015) - Montefusco, Anna; Semitaio, Giuliana; Marrese, Pier Paolo; Iurlaro, Andrea; De Caroli, Monica; Piro, Gabriella; Dalessandro, Giuseppe; Lenucci, Marcello Salvatore
Abstract : We report the hydrophilic and lipophilic antioxidant activities, as well as the total phenol, flavonoid, tocochromanol (tocopherol and tocotrienol), and carotenoid contents in the edible portion of wild and cultivated varieties of chicory ( Cichorium intybus L.) and in the basal rosette leaves of the wild species of poppy ( Papaver rhoeas L.), known by natives as "paparina, " collected in the countryside of Salento (South Apulia, Italy). We analyzed (1) two cultivars of chicory, the "Catalogna" harvested in the area between S. Pietro Vernotico and Tuturano (Brindisi) and the "Otrantina" harvested in Otranto (Lecce); (2) two wild chicory ecotypes harvested in S. Pietro Vernotico (Brindisi) and Statte (Taranto), respectively; (3) the basal leaves of wild poppy harvested in Sternatia (Lecce). In all samples, our results showed that the hydrophilic antioxidant activity is, generally, higher than the lipophilic activity. Poppy leaves exhibited the highest hydrophilic and lipophilic antioxidant activities and the highest concentration of total phenols and flavonoids. Tocopherols were detected only as traces. Among the extracted carotenoids, lutein and β -carotene were the most abundant in all analyzed samples. Total carotenoid content was greater in wild than in cultivated plants.